Contrast enhanced ultrasound for characterization of suspected soft tissue vascular anomalies. Issue 153 (August 2022) - Sangwan, Ankit; Goyal, Ankur; Kumar, Atin; Sharma, Raju; Bhalla, Ashu Seith; Kandasamy, Devasenathipathy; Arava, Sudheer; Singhal, Maneesh; Khandpur, Sujay
Highlights: Different vascular anomalies had distinctive temporal and morphological subjective enhancement patterns, helpful in characterization. Quantitative parameters like rise-time, mean-transit-timeand wash-in-rate showed significant differences amongst entities. Addition of contrast enhanced ultrasound not only increased the diagnostic accuracy of Doppler ultrasound but also the degree of diagnostic confidence. Abstract: Background: Evaluation of perfusion characteristics is the key to characterize vascular anomalies. Contrast-enhanced ultrasound (CEUS) is a radiation-free modality to evaluate this in real-time and can be coupled along with Doppler-ultrasound (US). Objective: To evaluate the utility of CEUS in characterization of suspected soft-tissue vascular anomalies and compare its diagnostic accuracy with Doppler-US. Materials and methods: This was an ethically-approved cross-sectional study, done from November 2017- November 2019, involving 93 patients (55 M/38F; mean age 23.6 ± 11.9 years) in development cohort and 128 (66 M/62F; mean age 21.4 ± 11.1 years) in validation cohort. Patients suspected to have soft-tissue vascular anomalies on clinical evaluation and US were included. Clinical features, US, Doppler, subjective and quantitative CEUS features (from time-intensity curves) were evaluated. Composite gold standard employing MRI, phlebogram, DSA or biopsy was used to make the final diagnosis. The CEUS features found to be significantly different in the development cohort were prospectively validated in the validation cohort. P-value < 0.05 was considered significant, ROC curves were drawn and threshold values obtained for the various quantitative parameters. A prospective diagnosis was suggested in the validation group along with a degree of diagnostic confidence and accuracy was calculated. Results: The spectrum of lesions included 77 venous malformations, 46 fibro-adipose vascular anomalies, 32 vascular tumors, 20 arteriovenous malformations and 20 lymphatic malformations. All lesions were found to have distinctive temporal and morphological subjective enhancement patterns. Quantitative parameters like rise-time, mean-transit-time, time-to-peak, peak-enhancement showed significant differences between the various groups (P value < 0.05). Addition of CEUS not only increased the diagnostic accuracy of Doppler-US from 76.5% (91/119) to 88.2% (105/119), but also the degree of diagnostic confidence in characterization of soft-tissue vascular anomalies. None of the patients showed any contrast-related adverse effects. Conclusion: Contrast-enhanced ultrasound is useful to characterize different types of soft-tissue vascular anomalies and increases the diagnostic accuracy and confidence over Doppler-ultrasound.